Python Source Code Plagiarism Attacks in Object-Oriented Environment - Oscar Karnalim; Aldi Aldiansyah (Computer Engineering and Applications Journal, 2017)
Since source code plagiarism is an emerging issue on Computer Science major and Python is a new popular programming language, this paper aims to empirically enlist plagiarism attacks that might be occurred on Python source code. As our case study, our work will be focused on source code plagiarism in object-oriented environment. The result of this work is expected to become either an evaluation baseline or a prior knowledge for developing Python-targeted plagiarism detection system. Based on 280 plagiarism-suspected pairs that were extracted from four Basic Data Structure classes, four findings can be deducted. First, there are 20 distinct Python plagiarism attacks that might be occurred in object-oriented environment. Second, plagiarism attack trend on both object-oriented and procedural environment are considerably similar to each other. Third, there is no need to handle plagiarism attacks in both object-oriented and procedural environment separately. Last, plagiarism attacks in object-oriented environment is more monotonous than such attacks in procedural environment.